Diagnostic accuracy of WHO verbal autopsy tool for ascertaining causes of neonatal deaths in the urban setting of Pakistan: a hospital-based prospective study. Issue 1 (December 2015) - Soofi, Sajid; Ariff, Shabina; Khan, Ubaidullah; Turab, Ali; Khan, Gul; Habib, Atif; Sadiq, Kamran; Suhag, Zamir; Bhatti, Zaid; Ahmed, Imran; Bhal, Rajiv; Bhutta, Zulfiqar
Abstract Background Globally, clinical certification of the cause of neonatal death is not commonly available in developing countries. Under such circumstances it is imperative to use available WHO verbal autopsy tool to ascertain causes of death for strategic health planning in countries where resources are limited and the burden of neonatal death is high. The study explores the diagnostic accuracy of WHO revised verbal autopsy tool for ascertaining the causes of neonatal deaths against reference standard diagnosis obtained from standardized clinical and supportive hospital data. Methods All neonatal deaths were recruited between August 2006 –February 2008 from two tertiary teaching hospitals in Province Sindh, Pakistan. The reference standard cause of death was established by two senior pediatricians within 2 days of occurrence of death using the International Cause of Death coding system. For verbal autopsy, trained female community health worker interviewed mother or care taker of the deceased within 2–6 weeks of death using a modified WHO verbal autopsy tool. Cause of death was assigned by 2 trained pediatricians. The performance was assessed in terms of sensitivity and specificity. Results Out of 626 neonatal deaths, cause-specific mortality fractions for neonatal deaths were almost similar in both verbal autopsy and reference standard diagnosis. Sensitivity of verbal autopsy was more than 93 % for diagnosing prematurity and 83.5 % for birth asphyxia. However the verbal autopsy didn't have acceptable accuracy for diagnosing the congenital malformation 57 %. The specificity for all five major causes of neonatal deaths was greater than 90 %. Conclusion The WHO revised verbal autopsy tool had reasonable validity in determining causes of neonatal deaths. The tool can be used in resource limited community-based settings where neonatal mortality rate is high and death certificates from hospitals are not available.